Abnormalities of Psycho-Emotional State among Patients with Excoriated Acne - E. A. Il’chevskaya; Yu. M. Krinitsyna; I. G. Sergeeva (Vestnik Dermatologii i Venerologii, 2018)
The psychopathological features of patients with excoriated acne are analysed. An integrative anx-iety test among 43 patients (mean age 24.7±7.1 years) demonstrated borderline values and a high level of personal anxiety in 46.5% of cases; assessment according to the Beck Depression Inventory revealed subdepression among 25.6% and depression among 13.9% of patients; the Global Severity Index (GSI) of the Symptom Checklist-90-R (SCL-90-R) was in the zone of elevated and high val-ues among 31.1% of patients. The greatest deviations from the norm were observed in the areas of interpersonal sensitivity among 34.9% of patients; dev phobic anxiety – 30.2%; paranoia – 30.2%; while somatisation of complaints was observed among 27.9% of patients. The obsessive-compulsive subscale exceeded normative values among 21% of patients.